ChatGPT sebagai Alat Bantu dalam Penulisan Karya Ilmiah Mahasiswa: Analisis Keterlibatan dan Kreativitas - Yasmine, Yuliana Sventy; Hikmawan, Rizki (Jurnal Pendidikan Informatika (EDUMATIC), 2025)
The field of education is facing challenges due to the emergence of various artificial intelligence technologies, one of which is the latest version of ChatGPT-4o. This version is more human-like and feature-rich, making it an effective feedback tool for assisting in the preparation of scientific papers. However, its role raises concerns among educators, as it has the potential to affect student engagement and creativity. This study aims to analyze the impact of using ChatGPT on student engagement and creativity in writing scientific papers. A quantitative approach using a survey method was conducted with 170 students from the Information Technology Systems Education program at a state university in Indonesia. Data were collected through a 29-item questionnaire using a four-point Likert scale to minimize ambiguity in respondents' answers. The data were then analyzed using descriptive and inferential statistics. Based on the results of the coefficient of determination analysis, ChatGPT usage was found to influence writing engagement by 25.3% and creativity by 8.10%. In addition to providing corrections, ChatGPT also offers suggestions and generates new ideas, enhancing interactive participation in the writing process. However, it may reduce students' reliance on more valid feedback sources, potentially impacting engagement and decreasing creativity in writing. These findings highlight the importance of ethical awareness among students and the need for educational institutions to develop strategies to mitigate the negative effects of ChatGPT in scientific writing.